Hydrogen Energy Challenges and Perspectives - Minic, Dragica (IntechOpen, 2012)
Hydrogen economy represents the future of human civilization. Limited resources of our planet are compelling us to turn to renewable clean energy resources and hydrogen figures prominently as the energy carrier of a future sustainable energy system. There are significant challenges to be overcome in order to make hydrogen viable, in production, storage and power generation, while safety of operation is an ever-present factor that determines success or failure of a proposed solution. Recent developments in all of these aspects are reviewed in this book, along with some latest research in the field of hydrogen energy and use.